A Study on Agricultural Marketing in India (International Journal of Food and Nutritional Sciences, 2022)
Agriculture is the backbone of our country. India is currently the world's second largest producer of 4,444 varieties of fruits and vegetables. Agricultural marketing information is essential information to promote agricultural growth in rural areas. Her agriculture in India continued to support, directly or indirectly, most of the population. Indian culture has served as a valuable tool for economic development as other sectors of production depend on it. Cooperative appears to be well positioned to coordinate product differentiation at the farm level and integrate into value-added processing activities. His current study focuses on past and current scenarios, challenges and future recommendations for prevalent agricultural marketing in India. Additionally, marketers need to effectively leverage the opportunities offered by agricultural marketing.